2018
DOI: 10.1159/000487678
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Autophagy Attenuated Ethylene Glycol Induced Crystals Deposition and Renal Injury in a Rat Model of Nephrolithiasis

Abstract: Background/Aims: Nephrolithiasis is a common and frequently occurring disease, its exact pathogenesis is remains unclear. Emerging data suggest that autophagy plays a vital role in the pathophysiological processes of kidney diseases. Therefore, this study was designed to investigate the potential role of autophagy in the formation of calcium oxalate (CaOx) kidney stones in rat model. Methods: Thirty-two rats were randomly divided into four groups (eight rats/group): untreated control group, stone model group, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…Consistent with our results, H19 has been recognized as an inflammatory regulator that triggers the immune response and induces tissue injury [10], [11], [12]. In addition, a recent study reported that autophagy was an important regulator in the formation and progression of kidney stone disease, and the inhibition of autophagy could decrease kidney injury and crystal deposition in an ethylene glycol-induced rat model of nephrolithiasis [22]. H19 was also reported to be involved in the regulation of autophagy.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our results, H19 has been recognized as an inflammatory regulator that triggers the immune response and induces tissue injury [10], [11], [12]. In addition, a recent study reported that autophagy was an important regulator in the formation and progression of kidney stone disease, and the inhibition of autophagy could decrease kidney injury and crystal deposition in an ethylene glycol-induced rat model of nephrolithiasis [22]. H19 was also reported to be involved in the regulation of autophagy.…”
Section: Discussionsupporting
confidence: 90%
“…Tubule calcium reabsorption in patients with hypercalciuria is reduced compared with that of patients with normal calcium excretion [3]. Emerging evidence indicates that autophagy and inflammatory responses are related to the formation of CaOx nephrolithiasis [4, 5]. Our previous study demonstrated that hypercalciuria may result in increased urinary excretion of various inflammatory cytokines, such as high-mobility group box-1 (HMGB1) and monocyte chemotactic protein-1 [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous evidence showed that the level of autophagy in patients with CaOx kidney stones was significantly higher than that in healthy controls and CaOx crystals promoted the production of ROS in RTEC, which mediated the activation of autophagy [ 9 , 10 ]. On the contrary, the inhibition of autophagy effectively attenuated CaOx crystals-induced oxidative stress damage, mitochondrial injury, urinary oxalate excretion, renal crystal deposition, and finally inhibited the formation of CaOx crystals in rat kidneys [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%